2020
DOI: 10.1016/j.jped.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived body image, dissatisfaction with body weight and nutritional status of Brazilian adolescents: a nationwide study

Abstract: Most of the sample rightly self-perceived their body image according to body mass index. Students with body image misperception and those dissatisfied with their weight were more likely to present a positive screening for common mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 24 publications
6
55
0
8
Order By: Relevance
“…Adolescents, however, have difficulties with an adequate assessment of their body weight, and often overestimate or underestimate their body weight. Studies showed that the body weight perception depended on the age and gender of respondents [2,6,28,29]. In a representative HBSC study, conducted in Poland in 2018 among 5225 students aged 11-15 years, only half of adolescents with normal body weight were able to properly assess their body weight.…”
Section: Dissatisfaction With Body Weight and Socio-demographic Factorsmentioning
confidence: 99%
“…Adolescents, however, have difficulties with an adequate assessment of their body weight, and often overestimate or underestimate their body weight. Studies showed that the body weight perception depended on the age and gender of respondents [2,6,28,29]. In a representative HBSC study, conducted in Poland in 2018 among 5225 students aged 11-15 years, only half of adolescents with normal body weight were able to properly assess their body weight.…”
Section: Dissatisfaction With Body Weight and Socio-demographic Factorsmentioning
confidence: 99%
“…In Brazil, the setting of this study, overall BWD ranges from 20% to 60% among adolescents [14,15]. However, few studies have investigated the association between BWD and behaviors related to cardiovascular risk in Brazilian adolescents, such as tobacco use [9], alcohol use [9] and physical inactivity [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported also a lower discordant weight perception among younger adolescents' girls [24], [25]. In fact, female adolescents are more likely to be exposed to thin ideal internalization through media, which has been proven influence body image, which have contributed to their body image disturbance [26], [27].…”
Section: Discussionmentioning
confidence: 88%
“…As they go through puberty, adolescents develop fat deposits on their body that are associated with changes in their body shape and increase in BMI, which has a significant influence on their body image [28]. On the other hand, sociocultural pressures that favor thinness as the ideal have a strong effect on body image, especially among adolescent [26]. However, another study determined that body weight dissatisfaction was not associated to age, but it was associated to BMI and sex [7].…”
Section: Discussionmentioning
confidence: 99%